A Study on Durability of a Fragrance Finishing on Jute Fabric - Lakshmanan Ammayappan; Nimai Chandra Pan; Sujay Chakraborty; Amlesh Khan (Journal of Natural Fibers, 2020)
Literature information on development of jute-based home textiles with an esthetic appeal and sustainable fragrance still lacks. A fragrance finish has been applied on a bleached jute fabric and the durability of the fragrance against home laundering was assessed by subjective assessment, scanning electron microscopic (SEM), moisture regain (%), Fourier transform infrared spectroscopy (FTIR), and handle property. Results inferred that microencapsulated fragrance sustains on the jute fabric up to 10 washing cycles.